Biochemical mechanisms and molecular interactions of vitamins in cancer therapy - Abdullahi T. Aborode; Isreal A. Onifade; Mercy M. Olorunshola; Gladys O. Adenikinju; Ibude J. Aruorivwooghene; Adeboboye C. Femi; Osasere Jude-Kelly Osayawe; Abraham Osinuga; Ebenezer A. Omojowolo; Adekunle F. Adeoye; Segun Olapade; Ibrahim O. Adelakun; et al. (Cancer Pathogenesis and Therapy)
Recently, the potential role of vitamins in cancer therapy has attracted considerable research attention. However, the reported findings are inconsistent, with limited information on the biochemical and molecular interactions of different vitamins in various cancer cells. Importantly, the presence of vitamin receptors in tumor cells suggests that vitamins play a significant role in the molecular and biochemical interactions in cancers. Additionally, studies on the efficacy of vitamin supplementation and dosage levels on tumor progression and mortality risk have yielded inconsistent results. Notably, molecular and biochemical investigations have reported the function of vitamins in the proliferation, growth, and invasiveness of tumor cells, as well as in cell cycle arrest and inflammatory signaling. Additionally, different vitamins may regulate the cancer microenvironment by activating various molecular pathways. Vitamins significantly affect immunological function, antioxidant defense, inflammation, and epigenetic control, and can improve treatment outcomes by affecting cell behavior and combating stress and DNA damage. However, further research is necessary to confirm the efficacy of vitamins, establish ideal dosages, and develop effective cancer prevention and treatment plans. Individualized supplementation plans guided by medical knowledge are crucial to achieving optimal results in clinical and preclinical settings. In this review, we critically evaluated the effects of different vitamins on the risk and development of cancer. Additionally, we examined the potential of vitamin supplements to enhance the efficacy of drug therapy and counteract resistance mechanisms that often arise during cancer treatment.